Chemical disinfection of non-porous inanimate surfaces experimentally contaminated with four human pathogenic viruses. - Sattar, S. A. (Cambridge University Press, 1989)
The chemical disinfection of virus-contaminated non-porous inanimate surfaces was investigated using coxsackievirus B3, adenovirus type 5, parainfluenza virus type 3 and coronavirus 229E as representatives of important nosocomial viral pathogens. A 10 microliter amount of the test virus, suspended in either faeces or mucin, was placed onto each stainless steel disk (about 1 cm in diameter) and the inoculum allowed to dry for 1 h under ambient conditions. Sixteen disinfectant formulations were selected for this study based on the findings of an earlier investigation with a human rotavirus. After 1 min exposure to 20 microliters of the disinfectant, the virus from the disks was immediately eluted into tryptose phosphate broth and plaque assayed. Using an efficacy criterion of a 3 log10 or greater reduction in virus infectivity titre and irrespective of the virus suspending medium, only the following five disinfectants proved to be effective against all the four viruses tested: (1) 2% glutaraldehyde normally used as an instrument soak, (2) a strongly alkaline mixture of 0.5% sodium o-benzyl-p-chlorophenate and 0.6% sodium lauryl sulphate, generally used as a domestic disinfectant cleaner for hard surfaces, (3) a 0.04% solution of a quaternary ammonium compound containing 7% hydrochloric acid, which is the basis of many toilet bowl cleaners, (4) chloramine T at a minimum free chlorine level of 3000 p.p.m. and (5) sodium hypochlorite at a minimum free chlorine concentration of 5000 p.p.m. Of those chemicals suitable for use as topical antiseptics, 70% ethanol alone or products containing at least 70% ethanol were ineffective only against coxsackievirus B3. These results emphasize the care needed in selecting chemical disinfectants for routine use in infection control.